Analisis Frase Nomina pada Teks Opini dalam Website Sevima Edisi Januari 2025 sebagai Bahan Bacaan dan Sumber Informasi Mahasiswa - Della Rohmatul Husnah; Anggie Aurellia Majid; Najwa Firlia Salsabilla; Nailatun Rochmaniah Prameswari; Dita Aditya Prananda; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Oktarina Puspita Wardani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
We have recognized various types of text, including opinion text. An opinion text is a text that contains the author's opinion or assessment of an object. A text, especially an opinion text, uses various types of phrases, one of which is noun phrases. A noun phrase is a phrase that can occupy the function of a subject or object in a clause. This research aims to analyze the coordinative and subordinative noun phrases in opinion texts on the January 2025 edition of the Sevima website. A qualitative descriptive approach is used as the methodology of this research, and a syntactic approach is used as the theoretical approach. The data collection technique used by the writer is a listening and note-taking technique, where the writer, in this study, reads several related references and records information that can be used as data. The data used in this study are opinion texts in the January 2025 edition of the Sevima website. The data analysis method used in this article is the agih method, using several stages, namely listening, analyzing, recording, and determining the use of noun phrases. The data findings in this study are that, in the opinion text, there are as many as 60 noun phrases with different structures and constructions. Much as 6 data include coordinative noun phrases (FNK) and 54 others are subordinative noun phrases (FNS). The results also show that subordinate noun phrases with the structure/construction of N+N and N+V phrases are the most widely used constructions in the opinion texts. With this research, it is hoped that it can be a source of learning for the community, especially students and researchers. The researcher also hopes that future studies on noun phrases can improve the shortcomings of this research.